1976
DOI: 10.1210/endo-98-2-336
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Somatostatin and Somatostatin Analogs on Inhibition of Arginine-Induced Insulin and Glucagon Release in the Rat

Abstract: Somatostatin and dihydrosomatostatin (H2somatostatin) are equipotent in inhibiting insulin and glucagon release induced by arginine in the rat. The ID50 of H2somatostatin on insulin and glucagon secretion induced by arginine are 14 +/- 6 and 6 +/- 10 mug/100 g BW respectively, similar to the ID50 of H2somatostatin (18 +/- 10 mug/100 g BW) on inhibition of insulin release induced by glucose. Thyrotropin releasing factor, luteinizing hormone releasing factor, alpha-MSH, and the N-terminus decapeptide of the beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…This is in agreement with the observation that both Ala2 and D-Ala2-somatostatin are more potent with respect to inhibition of GH, insulin and glucagon secretion than is cyclic-somatostatin Brown et al 1976a).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with the observation that both Ala2 and D-Ala2-somatostatin are more potent with respect to inhibition of GH, insulin and glucagon secretion than is cyclic-somatostatin Brown et al 1976a).…”
Section: Discussionsupporting
confidence: 92%
“…It therefore seems probable that the indole ring is important to position 8 (Rivier et al 1976). The increased activity of D-Trp8-somatostatin against the secretion of GH, insulin and glucagon is not due to increased duration of action (Brown et al 1976a). However, it has been reported that D-Trp8-somatostatin is less susceptible to in vitro enzymic degradation by rat and human plasma (Benuck & Marks, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in the D-amino acid substitution series, each amino acid was replaced with its D-isomer, thus changing the backbone conformation of the molecule. This series was of particular interest because of the dissociation of biologic activities that certain analogs exhibited in other systems (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%